Investigation of the Impact of One Thousand and One Nights on Pioneers of Arabic Modern Plays - Gholamabbas Rezaee Haftadar; Zeinab Ghasemi Asl (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2012)
With respect to the great impact of the One Thousand and One Nights on various literary and cultural arenas of the world nations, this study is conducted in order to investigate its role in flourishing modern Arab plays. For this purpose, after investigating roots and origins of plays and different forms of dramatic arts in Arab countries, this paper introduces One Thousand and One Nights and its dramatic capabilities. In concurrence with the formation of modern arab theatre and its foundation by great arab dramatists, a new wave of impression of One Thousand and One Nights on Arabic literature emerged, this time in the play area. Investigation and introduction of the most important plays written on the basis of this book constitute the next section of this research. This study tries to show the daramatic capabilities of One Thousand and One Nights through investigating the samples as well as introducing the wave of impression of Arab authors in the booming era of drama since the second half of the nineteenth century. This paper also intends to prove that the attention of the pioneers and founders of Arab drama is more focused on the historical heritage of the Arabic literature in general and One Thousand and One Nights in particular as compared to European literature.